2020
DOI: 10.18521/ktd.733639
|View full text |Cite
|
Sign up to set email alerts
|

Sağlık Bilimleri Fakültesi Öğrencilerinin Sağlıklı Beslenme ve Fiziksel Aktiviteyle İlgili Tutumlarının Değerlendirilmesi

Abstract: The foundations of a healthy life are laid during youth, and healthy nutrition and regular physical activity are not only two key determinants of health but also two main factors decreasing age-related health risks. Universities are the ideal environments for increasing this awareness and educating university students that constitute the majority of young population on healthy behavioral choices. This study aimed to evaluate the factors affecting the attitudes of the students of the Faculty of Health Sciences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Alzamil H et al 2019 agreed with the present study and found that; high proportion of the participants consumed breakfast or vegetables 5 days per week, whereas the corresponding proportions for fresh fruit were low adding; proportions of college females who consumed less healthy foods for 3 and more times per day every week were ranging from 21.1% for French fries to 60.4% for chocolates and or candy [8]. The main finding of Hassan et al's study was that university students have unhealthy eating practices [16], Further, Gunes F et al, found that fewer than half of their participants ate the daily recommended amount of fruits and vegetables [17], these findings also were consistent agreed and supported with previous research results on college students from different countries [2,[18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 77%
“…Alzamil H et al 2019 agreed with the present study and found that; high proportion of the participants consumed breakfast or vegetables 5 days per week, whereas the corresponding proportions for fresh fruit were low adding; proportions of college females who consumed less healthy foods for 3 and more times per day every week were ranging from 21.1% for French fries to 60.4% for chocolates and or candy [8]. The main finding of Hassan et al's study was that university students have unhealthy eating practices [16], Further, Gunes F et al, found that fewer than half of their participants ate the daily recommended amount of fruits and vegetables [17], these findings also were consistent agreed and supported with previous research results on college students from different countries [2,[18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 77%
“…Numerous studies have shown that attitude toward physical exercise is closely correlated with health-related behavior. A recent study on college students indicated that a healthy diet and an attitude toward physical exercise can promote the cultivation of a healthy lifestyle [ 24 ]. College students should be fully aware of the potential health threats of poor eating habits and being overweight.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…During the period of their academic studies (late youth), students should be physically and mentally healthy, practicing an active life and having healthy eating behaviors to maintain their health status. They need a good physical and mental condition to cope with the effort required during their academic years and to have a satisfactory body image [ 5 , 8 ]. A poor perception of well-being can lead to less involvement in good self-care practices or poor adherence to interventional programs, while a perceived good or excellent level of well-being is associated with good personal care [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such means of mass communication and various sociocultural pressures are considered to cause an increased awareness of being thin as an ideal and contribute to the misperception of body weight [ 17 ]. Media has a significant impact on body image as a powerful force that uses various aspects, including the internet, television, magazines, video games, and smartphones to present the ideal of beauty [ 8 ]. Currently, media promotes a slim figure model among women and muscular/athletic figure among men, promoting foods and diets with inadequate nutritional value, which can also lead to unwanted nutritional and health behaviors and the nonacceptance of body weight [ 7 ].…”
Section: Introductionmentioning
confidence: 99%